Building Practical High‐Voltage Cathode Materials for Lithium‐Ion Batteries (Adv. Mater. 52/2022). Issue 52 (28th December 2022) - Xiang, Jingwei; Wei, Ying; Zhong, Yun; Yang, Yan; Cheng, Hang; Yuan, Lixia; Xu, Henghui; Huang, Yunhui
Abstract : Lithium‐Ion Batteries One of the most effective strategies for boosting the energy density of lithium‐ion batteries (LIBs) is to increase the output voltage, which largely depends upon the cathode materials. In article number 2200912, Lixia Yuan, Henghui Xu, Yunhui Huang, and co‐workers review the key links in the development of high‐voltage cathode materials from lab to industrialization and give future perspectives for designing practical high‐voltage cathode materials for LIBs.